357 Early life factors shaping gut development and lifelong disease risk. (30th November 2020) - Moeser, Adam J
Abstract: The first 3–4 months of postnatal life represents a critical period in gastrointestinal (GI) development that shapes lifelong function and disease resistance. During this period, extensive maturation of the immune and nervous systems, and epithelial transport and barrier function, occurs. While some aspects of early life gut development are genetically "hard-wired, " the GI system exhibits a high degree of plasticity, and thus developmental trajectory and long-term function can be significantly modified during this period via host and environmental influences. Stress or adversity during early critical periods of development has been recognized as a significant risk factor for the later-life susceptibility to several GI and systemic chronic inflammatory and debilitating diseases in humans and animals, including functional bowel disorders characterized by dysmotility and neuroinflammation, but also disease associated with systemic inflammation, such as metabolic disorders (obesity and Type 2 diabetes) and neurobehavioral disorders including anxiety and depression. Moreover, early life stressors include routine management practices such as maternal separation and early weaning, social disruption, and early immune activation from disease or vaccination, and thus early life stress is common in animals. While the link between early life adversity and later life disease risk is well-established across species, the mechanisms that link early life stress, gut development and lifelong disease risk are poorly understood, and thus targeted management, therapeutic and nutritional strategies to reduce the negative impacts of early life stress are lacking. This goal of this presentation is to provide a biological framework for understanding how early life environmental and host factors such as stress and biological sex can alter the normal trajectory of GI development and disease risk throughout the lifespan. Ways in which changes in gut development might drive the risk for diseases important to many species, such as metabolic disease, functional/inflammatory bowel disorders and neurobehavioral disorders, will be discussed.